Problematika Etis Penyalahgunaan Dana Bantuan Mengatasnamakan Kemanusiaan - Yonathan Wingit Pramono; Priyantoro Widodo (Institut Agama Kristen Negeri Kupang, 2021)
The protracted conflict between Israel and Palestine until now, heated up again after the incident at the Al Aqsa Mosque, made many sympathetic people to raise aid funds, using the momentum in this incident. Misuse of aid funds in the name of Palestine is likely to occur, with the phenomenological method of seeking information on various social media with events that occur in the community, so that the misuse of aid funds in the name of Palestine is reduced and can be distributed properly. regents, can make fundraising activities right on target and carried out with clear reports to the community in their management.